Spoiled distinctions : aesthetics and the ordinary in French modernism - Freed-Thall, Hannah (Oxford University Press, 2015)
'Spoiled Distinctions' charts 20th-century experiments in the aesthetics of the ordinary, arguing that Proust and his literary and philosophical successors (Francis Ponge, Nathalie Sarraute, Yasmina Reza, Pierre Bourdieu, and Roland Barthes, among others) multiply strategies for reading and valuing the everyday. These authors explore the unsophisticated side of aesthetic experience. Alert to the ways in which the hunger for distinction shapes mundane acts of seeing and feeling, they strive to imagine less exclusive practices of art-making and of aesthetic perception.